Shape matters: the complex relationship between aggregation and toxicity in protein-misfolding diseases - Ries, Heidrun Maja; Nussbaum-Krammer, Carmen (Essays in biochemistry, 2016)
A particular subgroup of protein-misfolding diseases, comprising Alzheimer's and Parkinson's disease, involves amyloidogenic proteins that can form alternative pathogenic conformations with a high tendency to self-assemble into oligomeric and fibrillar species. Although misfolded proteins have been clearly linked to disease, the exact nature of the toxic species remains highly controversial. Increasing evidence suggests that there is little correlation between the occurrence of macroscopic protein deposits and toxic phenotypes in affected cells and tissues. In this article, we recap amyloid aggregation pathways, describe prion-like propagation, elaborate on detrimental interactions of protein aggregates with the cellular protein quality control system and discuss why some aggregates are toxic, whereas others seem to be beneficial. On the basis of recent studies on prion strains, we reason that the specific aggregate conformation and the resulting individual interaction with the cellular environment might be the major determinant of toxicity.